A complex system for the production of pathogen-free grapevine propagating material - Bisztray, Gy. D.; Lázár, J.; Szegedi, E.; Varga, G.; Nagy, B.; Hajdu, E. (International Journal of Horticultural Science, 2011)
The use of pathogen-free planting stock for new vineyard establishment is a key component in the maintenance and expansion of vine and quality table grape production. The success of the necessary changes in the structure of the grape industry is forced by the globalization process, the climate change, the rediscovery of autochton varieties as well as breeding of new tolerant and resistant varieties. The renewal of vineyards largely depend on the availability of planting stocks. Serbia and Hungary found a common interest in establishing pathogen-free stock materials from newly breed resistant varieties and clonal selections of varieties which are traditional in the Serbian-Hungarian border area. During a cross-border cooperation program a complex system for the production of pathogen-free grapevine propagating material was established. Using heat therapy, in vitro shoot tip culture and traditional and molecular diagnostic techniques new pathogen-free stock materials were established from 26 varieties. They have been or will be tested for the presence of most important grapevine viruses, phytoplasmas, as well as bacterial and fungal pathogens. The complex system applying green grafting for indexing on grapevine indicators can shorten the duration of the procedure from 4 years to two-three years.